Why do arms extract less oxygen than legs during exercise? - Calbet, J. A. L.; Holmberg, H. C.; Rosdahl, H.; van Hall, G.; Jensen-Urstad, M.; Saltin, B. (American Journal of Physiology - Regulatory, Integrative and Comparative Physiology, 2005)
To determine whether conditions for O2 utilization and O2 off-loading from the hemoglobin are different in exercising arms and legs, six cross-country skiers participated in this study. Femoral and subclavian vein blood flow and gases were determined during skiing on a treadmill at ?76% maximal O2 uptake (O2 max) and at O2 max with different techniques: diagonal stride (combined arm and leg exercise), double poling (predominantly arm exercise), and leg skiing (predominantly leg exercise). The percentage of O2 extraction was always higher for the legs than for the arms. At maximal exercise (diagonal stride), the corresponding mean values were 93 and 85% (n = 3; P < 0.05). During exercise, mean arm O2 extraction correlated with the PO2 value that causes hemoglobin to be 50% saturated (P50: r = 0.93, P < 0.05), but for a given value of P50, O2 extraction was always higher in the legs than in the arms. Mean capillary muscle O2 conductance of the arm during double poling was 14.5 (SD 2.6) ml·min-1·mmHg-1, and mean capillary PO2 was 47.7 (SD 2.6) mmHg. Corresponding values for the legs during maximal exercise were 48.3 (SD 13.0) ml·min-1·mmHg-1 and 33.8 (SD 2.6) mmHg, respectively. Because conditions for O2 off-loading from the hemoglobin are similar in leg and arm muscles, the observed differences in maximal arm and leg O2 extraction should be attributed to other factors, such as a higher heterogeneity in blood flow distribution, shorter mean transit time, smaller diffusing area, and larger diffusing distance, in arms than in legs.